An aerial deployed unmanned glider for cross-Channel flight - Jabbal, Mark (Marques Aviation Press, 2015)
This paper describes the technical and operational challenges of the first cross-Channel flight performed by an unmanned autonomous glider. The glider chosen for the attempt was a quarter scale Slingsby Type 45 Swallow. It was found to have a lift-to-drag ratio of 8, as verified by wind tunnel force balance tests. Essential retrospective aerodynamic refinements to the design, including modifications of the wing root and tip sections and wing aspect ratio, were modelled analytically and found to increase the aircraft’s lift-to-drag ratio to 19. The launch mechanism devised for the modified glider featured a bespoke crate suspended under an airborne helicopter at an altitude of 10,000 ft, from which the aircraft was released from an internal recess. The glider was pre-programmed to fly autonomously via waypoint navigation and completed the 22 mile mission in less than one hour at an average ground speed of 27 knots, a sink rate of 3 ft/s and with 3,500 ft altitude to spare. The successful flight, which was filmed from onboard cameras and a chase helicopter, represents a unique first in autonomous aviation and is unofficially the longest straight distance flight for an unmanned engineless glider.